From Self-Compassion to Life Satisfaction: Examining the Mediating Effects of Self-Acceptance and Meaning in Life - Zipagan, Faye B. (Archīum Ateneo, 2023)
Objectives Despite the well-established link between self-compassion and subjective well-being, little is understood about the mechanisms of this relationship. This study aimed to determine whether self-acceptance and meaning in life act as mediators between self-compassion and life satisfaction. Method Using a cross-sectional survey design, this study utilized a sample of 178 Filipino adults. A mediation analysis was run using participants’ responses to the Self-Compassion Scale, Unconditional Self-Acceptance Questionnaire, Meaning in Life Questionnaire, and the Satisfaction With Life Scale. Results Self-acceptance was not a significant mediator (B = 0.12, SE = 0.19, 95% CI: [−0.296, 0.425]) while meaning in life had a significant mediating effect (B = 0.50, SE = 0.12, 95% CI: [0.271, 0.770]) between self-compassion and life satisfaction. When self-compassion was analyzed in terms of its components, the serial mediating effect of self-acceptance and meaning in life was found to be significant for common humanity (B = 0.18, SE = 0.09, 95% CI [0.036, 0.397]) and mindfulness (B = 0.17, SE = 0.08, 95% CI [0.032, 0.354]) but not for self-kindness (B = 0.09, SE = 0.07, 95% CI [−0.019, 0.259]). Conclusions These results contribute to the understanding of how overall and certain components of self-compassion predict life satisfaction. Focusing on meaning in life, and to a certain extent on self-acceptance, may potentially maximize the impact of self-compassion on life satisfaction. Preregistration This study is not preregistered.